Visiting Tianshui City: A Look into Martial Culture on China's Northern Silk Route - Stanley E. Henning (Universidad de León, 2012)
Tianshui city, located in China's ancient cultural center in Gansu Province, includes a large rural area known as Qinzhou. This area houses pockets of traditional martial arts culture, which allow one to savor the past in the present, even in the face of China's unprecedented economic development and social change in recent years. The picture described in this short article is based upon the author's visits to Tianshui, most recently in 2007, on-site discussions with Professor Cai Zhizhong, who teaches martial arts in the physical education program of Tianshui Normal College, and Professor Cai's writings on the subject. While the modernization taking place throughout China cannot help but have an inﬂuence on Tianshui's traditional martial arts practices, one comes away hopeful that the strong historical awareness and sense of cultural pride exhibited by the area's residents will insure a continuing role for Tianshui's traditional martial arts.